(untitled) (Palimpsesto, 2017)
The essay analyses the development of the New Chilean cinema between 1957 and 1973, and reflects on the configuration of a political-pedagogical proposal in their work, defined on the basis of the relationship that sets this current with the popular sectors. It is argued that after an initial phase of re-discovery of what is popular, filmmakers and chileans documentalists have redefined their socio-political role in educational key, defining their work as a "pedagogical tool" of and for the popular field, making a distintion between two positions: the first considerates the cinema as a tactic of ideological clarification (Vanguard) and the other suggests a cinema as a tool of objectification and critical analysis of reality (similar to the proposal freiriana of awareness).